Sex differences in 10-year cardiovascular risk of patients with type 2 diabetes mellitus and subclinical hypothyroidism: a cross-sectional study - Zhao, Xiang; He, Ke; Li, Ji; Zhou, Lingyan; Liu, Ling; Lu, Xiwan; Jiang, Yan (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate gender-specific variations in cardiovascular disease (CVD) risk stratification and its modifiable determinants among individuals concurrently diagnosed with type 2 diabetes mellitus (T2DM) and subclinical hypothyroidism (SCH).MethodsA cross-sectional observational study was conducted involving 2,357 patients with T2DM (1,120 males and 1,237 females) who were hospitalized at Wuxi Hospital of Traditional Chinese Medicine between 2018 and 2024. Participants were categorized into the SCH (n=196) and the euthyroid subgroups (n=2,161). The 10-year probability of cardiovascular events was estimated based on the Framingham Risk Score (FRS) model. Sex-specific differences in SCH prevalence and CVD risk were examined, and associations between FRS and biomarkers—namely thyroid-stimulating hormone (TSH), free thyroxine (FT4), cystatin C (CysC) and other factors—were analyzed via Spearman’s correlation analysis and multivariable linear regression.ResultsThe prevalence of SCH in T2DM patients was 9.06% (10.02% in females vs. 6.43% in males). Male patients diagnosed with SCH exhibited an elevated FRS compared to their euthyroid counterparts (21.00 vs. 20.00, P= 0.025). Within this subgroup, a positive relationship was identified between TSH levels and FRS(r=0.374, P= 0.001), whereas FT4 showed a negative association (r=-0.342, P= 0.003). These relationships were not statistically significant among women diagnosed with SCH. Cystatin C was positively associated with FRS in both male (r=0.461, P<0.001) and female (r=0.452, P<0.001) groups. Multivariable linear regression evaluation in male patients revealed that TSH (β=3.87, P= 0.048), cystatin C (β=1.48, P= 0.03), and FT4 (β=-0.61, P= 0.011) continued to be significantly correlated with 10-year CVD risk. Additionally, male patients with SCH exhibited significantly higher smoking status, uric acid, and creatinine levels than their female counterparts (all P<0.05), indicating that sex-specific risk factors may contribute to elevated CVD risk.ConclusionThis study identified higher FRS in male versus female patients with comorbid T2DM and SCH, potentially mediated by sex-specific variations in TSH, FT4, and CysC levels. These results underscore the importance of implementing sex-specific strategies for CVD risk management in this population.